CALIBRATION OF EFFECTIVE SOIL HYDRAULIC PARAMETERS OF HETEROGENEOUS SOIL PROFILES - Jhorar R.K.; Van Dam J.C.; Bastiaanssen W.G.M.; Feddes R.A. (My University, 2004)
Distributed hydrological models are useful tools to analyse the performance of irrigation systems at different levels. For the successful application of these models, it is imperative that effective soil hydraulic parameters at the scale of model application are known. The majority of previous studies to define effective soil hydraulic parameters have considered only horizontal spatial variability of the parameters while neglecting textural layering at different spatial locations. In this paper, numerical experiments are conducted for seven vertical heterogeneous soil profiles (containing 4-5 soil layers) to generate different water balance components. Thereafter, information on evapotranspiration fluxes and water storage in the root zone profile is inversely used to identify effective soil hydraulic parameters. The aim is to assess whether effective soil hydraulic parameters can be assigned to vertically heterogeneous soil profiles. The performance of inversely identified soil hydraulic parameters is evaluated by their ability to reproduce the different components of water balance. Results showed that the evapotranspiration fluxes are sufficient to inversely identify soil hydraulic parameters for heterogeneous soil profiles under deep water table conditions and significant moisture stress. The identified soil hydraulic parameters are suitable to predict water balance components. However, appropriate formulation of soil evaporation simulation is very important if the surface soil layers have deviating soil hydraulic properties. Results also showed that general information on the textural layering of the area is an important input to inversely identify effective soil hydraulic parameters using evapotranspiration fluxes.
Keywords: HETEROGENEITY; SOIL PROFILES; WATER BALANCE; EFFECTIVE PARAMETERS; EVAPOTRANSPIRATION; INVERSE PROBLEM